A systematic approach to safety incidents in public health: Applying the human factors analysis and classification system to COVID-19 - Steve J. Bickley; Benno Torgler (Center for Research in Economics, Management and the Arts (CREMA), 2020)
In this article, we argue for application of the Human Factors Analysis and Classification System (HFACS) to proactive incidence prevention in the public health system response to COVID-19. HFACS is a framework of causal categories of human errors typically applied for systematic retrospective incident analysis in high-risk domains. By leveraging this approach proactively, appropriate, and targeted measures can be quickly identified and established to mitigate potential errors at different levels within the public health system (from frontline healthcare workers to regulatory and statutory decision makers).
Keywords: 330; Gesundheitswesen; Arbeitsunfall; Coronavirus; Gesundheitsvorsorge; Arbeitsschutz; Klassifikation